Local activation of coagulation and inhibition of fibrinolysis in the lung during ventilator associated pneumonia. Issue 2 (3rd February 2004) - Schultz, M J; Millo, J; Levi, M; Hack, C E; Weverling, G J; Garrard, C S; van der Poll, T
Abstract : Background: Fibrin deposition is a hallmark of pneumonia. To determine the kinetics of alterations in local coagulation and fibrinolysis in relation to ventilator associated pneumonia (VAP), a single centre prospective study of serial changes in pulmonary and systemic thrombin generation and fibrinolytic activity was conducted in patients at risk for VAP. Methods: Non-directed bronchial lavage (NBL) was performed on alternate days in patients expected to require mechanical ventilation for more than 5 days. A total of 28 patients were studied, nine of whom developed VAP. Results: In patients who developed VAP a significant increase in thrombin generation was observed in the airways, as reflected by a rise in the levels of thrombin-antithrombin complexes in NBL fluid accompanied by increases in soluble tissue factor and factor VIIa concentrations. The diagnosis of VAP was preceded by a decrease in fibrinolytic activity in NBL fluid. Indeed, before VAP was diagnosed clinically, plasminogen activator activity levels in NBL fluid gradually declined, which appeared to be caused by a sharp increase in NBL fluid levels of plasminogen activator inhibitor 1. Conclusion: VAP is characterised by a shift in the local haemostatic balance to the procoagulant side, which precedes the clinical diagnosis of VAP.